THE ROLE OF CHILDREN'S LITERATURE IN SPEECH DEVELOPMENT (Scientific journal of the Fergana State University, 2026)
Children's literature serves the development of logical coherence of speech, that is, speech coherence. Recounting literary works, creating stories based on pictures, and other creative activities ensure children's transition to coherent speech. The greater the importance of the word in ensuring the consistency of speech, the higher the advantage of fiction.